2012
DOI: 10.1016/s1413-8670(12)70293-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro study of the effect of a probiotic bacterium Lactobacillus rhamnosus against herpes simplex virus type 1

Abstract: The results of this study indicate that Lactobacillus rhamnosus enhances macrophage viability for HSV-1 elimination and activation against HSV-1 more effectively, when compared with non-probiotic Escherichia coli. it also seems that receptor occupation of macrophage sites decreases HSV-1 infectivity by both of the studied bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
0
16
0
1
Order By: Relevance
“…Other studies have found similar results in macrophage cultures using different probiotic strains [ 27 , 34 36 ]. Khani et al [ 30 ] also observed that live L . rhamnosus induced higher levels of TNF- α , suggesting that the entire bacteria promoted phagocytosis and consequently increased macrophage activation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found similar results in macrophage cultures using different probiotic strains [ 27 , 34 36 ]. Khani et al [ 30 ] also observed that live L . rhamnosus induced higher levels of TNF- α , suggesting that the entire bacteria promoted phagocytosis and consequently increased macrophage activation.…”
Section: Discussionmentioning
confidence: 99%
“…However, synbiotic supplementation for 6 weeks did not influence CRP values [ 41 ]. In addition, NO status did not affect by probiotic in herpes simplex virus type 1 [ 42 ]. Supplementation with probiotic supplements for 7 days did not decrease MDA values [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been an increased interest in using LAB and other probiotic bacteria as viral inhibitors against coronavirus (Maragkoudakis et al 2010), herpes simplex virus (Khani et al 2012), human immunodeficiency virus (Martín et al 2010), influenza virus (Kobayashi et al 2011;Lee et al 2013;Youn et al 2012), rotavirus (RV;Maragkoudakis et al 2010), and vesicular stomatitis virus (VSV; Botić et al 2007). Lactococcus lactis (formerly, Streptococcus lactis) is one of the most important LABs.…”
Section: Introductionmentioning
confidence: 99%